Analisis Profil Sensori Teh Buah Aneka Rasa dengan Metode CATA (Check-All-That-Apply) - Muhammad Fakih Kurniawan; Nindya Atika Indrastuti; Aviani Kurnianingrum (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Fruit tea is processed dried tea leaves mixed with dried fruit. One of the local brand fruit tea products circulating in the Indonesian market is Haveltea. The purpose of this study was to identify the sensory profiles of four fruit tea variants (peach flavored fruit tea, mango flavored fruit tea, lychee flavored fruit tea and bergamot orange flavored fruit tea) using CATA (check-all-that-apply). The methods consisted of two steps: determining sensory attributes of fruit tea using FDG (Forum Discussion Group) and sensory testing to 50 consumers. The analysis used in this CATA included Cochran’s Q-test, correspondence analysis, principal coordinate analysis (PCoA), and penalty analysis using the XLSTAT 2020 software. As a result, the four fruit teas have aroma characters (burned, roasted, tea, sweet and fresh or candied fruit), flavor (fermented, green, lime, lechy, peach and mango), taste (bitter and astringent), and aftertaste (astringent). According to consumer panelists, the ideal fruit tea product is fruit tea with the dominant attributes of fermented flavour, lechy flavor, peach flavor and mango flavour. Based on the results of PCoA and correspondence analysis, which was strengthened by counterplot preference mapping, the attributes of fermented flavour, peach flavor and lechy flavor could affect panelists preference for fruit tea samples and these attributes matched the attributes of the ideal product according to the panelists. Some sensory attributes are required that must be present and enhanced in products such as sweet aroma, lechy flavor and mango flavour. The most preferred fruit tea by consumers is lychee flavored fruit tea with a preference level of up to 71%